1991
DOI: 10.1111/j.1600-0528.1991.tb00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence and salivary mutans streptococci in 0–2‐year‐old children of Japan

Abstract: The prevalence of caries and the number and species distribution of salivary mutans streptococci in 356 children (aged 0-2 yr old) in Japan were examined twice at an interval of 1 yr. No mutans streptococci were isolated from the predentate children. The detection rate of mutans streptococci and the prevalence of caries increased with age. Mutans streptococci were isolated from 39.9% of the subjects. The majority of isolates were identified as Streptococcus mutans. The concentration of mutans streptococci corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
100
2
42

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(158 citation statements)
references
References 16 publications
14
100
2
42
Order By: Relevance
“…They are the most common pathogens isolated from human dental plaque and their prevalence has been reported in epidemiological studies (Hamada & Slade, 1980;Whiley & Beighton, 1998). S. mutans has been shown to be more prevalent than S. sobrinus in dental plaque samples (Loesche, 1986; Carlsson et al, 1987), while several epidemiological studies have shown that the prevalence of S. sobrinus is more closely associated with high caries activity (Fujiwara et al, 1991;Hirose et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are the most common pathogens isolated from human dental plaque and their prevalence has been reported in epidemiological studies (Hamada & Slade, 1980;Whiley & Beighton, 1998). S. mutans has been shown to be more prevalent than S. sobrinus in dental plaque samples (Loesche, 1986; Carlsson et al, 1987), while several epidemiological studies have shown that the prevalence of S. sobrinus is more closely associated with high caries activity (Fujiwara et al, 1991;Hirose et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…They are the most common pathogens isolated from human dental plaque and their prevalence has been reported in epidemiological studies (Hamada & Slade, 1980;Whiley & Beighton, 1998). S. mutans has been shown to be more prevalent than S. sobrinus in dental plaque samples (Loesche, 1986; Carlsson et al, 1987), while several epidemiological studies have shown that the prevalence of S. sobrinus is more closely associated with high caries activity (Fujiwara et al, 1991;Hirose et al, 1993).In several epidemiological studies, identification of S. mutans and S. sobrinus on selective media such as mitis-salivarius (MS) or MS-bacitracin (MSB) agar has been performed using colonial morphology (Wade et al, 1986;Svanberg & Krasse, 1990). However, accurate differentiation between S. mutans and S. sobrinus is not easy, and is also timeconsuming and laborious (de Soet et al, 1990).…”
mentioning
confidence: 99%
“…Se a colonização dos EM for retardada, a experiência de cárie da criança será menor, quando comparada com a daquelas colonizadas mais precocemente 2,14,19 . Por outro lado, foi demonstrado que o número de EM detectado na saliva das crianças correlaciona-se com a prevalência e incidência de cárie que experimentam 14,20,21 .…”
Section: Introductionunclassified
“…Se a colonização dos EM for retardada, a experiência de cárie da criança será menor, quando comparada com a daquelas colonizadas mais precocemente 2,14,19 . Por outro lado, foi demonstrado que o número de EM detectado na saliva das crianças correlaciona-se com a prevalência e incidência de cárie que experimentam 14,20,21 .Tendo como ponto de partida mães altamente colonizadas por EM aos dois meses e meio de idade dos seus primogênitos, e condições sócio-econômicas bastante semelhantes, este As crianças foram examinadas quanto ao número de dentes irrompidos e presença de cárie dental (índice ceos). Os níveis salivares de EM foram determinados em saliva não estimulada.…”
unclassified
See 1 more Smart Citation